Novas determinações do processo de reprodução do espaço da metrópole Manauara - Eduardo Henrique Freitas Braga (Confins)
The text tries to present, from some elements of an ongoing research, the reflection about the new determinations existing in the process of reproduction of the metropolitan space of Manaus. These so-called determinations are both of a new nature within the Amazonian urban context and of the contemporary urbanization process itself, which in a multi-scale relationship comprises both large regions and specific places of a specific territory. Here we have the state highway AM-070, located in the city of Iranduba and Manacapuru as a place of analysis, bringing in the recognition of the processes that are active in it, the possibilities of understanding these emerging dynamics. The establishment of a real estate sector and its varied products (condominiums, subdivisions) produces an abrupt new reality in this fragment of the territory, thus bringing challenges to understanding at the same time as its necessity.